22q11.2 Deletion Syndrome: Laboratory Diagnosis and TBX1 and FGF8 Mutation Screening - Sgardioli, Ilária C.; Vieira, Társis P.; Simioni, Milena; Monteiro, Fabíola P.; Gil-da-Silva-Lopes, Vera L. (Journal of Pediatric Genetics, 2015)
Velocardiofacial syndrome is one of the recognized forms of chromosome 22q11.2 deletion syndrome (22q11.2 DS) and has an incidence of 1 of 4,000 to 1 of 6,000 births. Nevertheless, the 22q11 deletion is not found in several patients with a 22q11.2 DS phenotype. In this situation, other chromosomal aberrations and/or mutations in the T-box 1 transcription factor C (TBX1) gene have been detected in some patients. A similar phenotype to that of the 22q11.2 DS has been reported in animal models with mutations in fibroblast growth factor 8 (Fgf8) gene. To date, FGF8 mutations have not been investigated in humans. We tested a strategy to perform laboratory testing to reduce costs in the investigation of patients presenting with the 22q11.2 DS phenotype. A total of 109 individuals with clinical suspicion were investigated using GTG-banding karyotype, fluorescence in situ hybridization, and/or multiplex ligation-dependent probe amplification. A conclusive diagnosis was achieved in 33 of 109 (30.2%) cases. In addition, mutations in the coding regions of TBX1 and FGF8 genes were investigated in selected cases where 22q11.2 deletion had been excluded, and no pathogenic mutations were detected in both genes. This study presents a strategy for molecular genetic characterization of patients presenting with the 22q11.2 DS using different laboratory techniques. This strategy could be useful in different countries, according to local resources. Also, to our knowledge, this is the first investigation of FGF8 gene in humans with this clinical suspicion.
Keywords: velocardiofacial syndrome; 22q11.2 deletion syndrome; laboratory diagnosis; TBX1; FGF83